PUBLICATION D’UN ARTICLE SCIENTIFIQUE - IKEKE, Jérôme MOLIMA; ASAKAET, Gabriel OMARY; MANONGO, Josée LISONGOMI (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
This drank is has self-study of the 18’s to 25-IN Influences of the HIV / AIDS, is the making of the man who accepted to answer our questionnaire is 70 cases, constituted of 41 boys and 29 girls. The questionnaire and the interview structured have been allowed to the collection of the data, we conducted their spoliation, to their treatment by the results. We made a calculation of percentage below on the statistical calculation:% = fo / N × 100. The calculation of percentage allowed us to analyze our results and to compare the previous works, the registration of our investigations, us have about the main following results; 18,6% of them investigated are the slice between 24; 58,6% of them investigated are of Masculine sex; 58,6% are students; 71,4% of them investigated are unmarried; 78,6% of people interrogated are of academic level; 53% of people interrogated are of believer protesting; The majority of people interrogated had knowledge of the VIH / AIDS; 54,2% of people interrogated received the information on the VIH in the university; 43,0% of people affected from the VIH / AIDS was reached of the human immunodeficiency syndrome; 80% of people interrogated confirmed the use of condom, as measure of struggle against the VIH / AIDS. Thus, we can say that our objectives have been reached